2019
DOI: 10.1080/03461238.2019.1655477
|View full text |Cite
|
Sign up to set email alerts
|

Bonus-Malus premiums under the dependent frequency-severity modeling

Abstract: In auto insurance, a Bonus-Malus System (BMS) is commonly used as a posteriori risk classification mechanism to set the premium for the next contract period based on a policyholder's claim history. Even though recent literature reports evidence of a significant dependence between frequency and severity, the current BMS practice is to use a frequency-based transition rule while ignoring severity information. Although Oh et al. (2019) claim that the frequencydriven BMS transition rule can accommodate the depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…In our analysis, longitudinal data over the policy years from 2006 to 2010 with 497 governmental entities are used. There are two categorical variables identical to the dataset studied in Oh et al [17]: the entity type with six levels and the coverage with three levels, as shown in Table B.4. Following this, we model the frequency part as | ( [1] , [1] ) ∼ Poisson( [1] [1] ) with [1] = exp( [1] [1] ), and the individual severity part as , | ( [2] , [2] ) ∼ Gamma( [2] [2] , 1/ [2] ) with [2] = exp( [2] [2] ),…”
Section: Data Description and Estimation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our analysis, longitudinal data over the policy years from 2006 to 2010 with 497 governmental entities are used. There are two categorical variables identical to the dataset studied in Oh et al [17]: the entity type with six levels and the coverage with three levels, as shown in Table B.4. Following this, we model the frequency part as | ( [1] , [1] ) ∼ Poisson( [1] [1] ) with [1] = exp( [1] [1] ), and the individual severity part as , | ( [2] , [2] ) ∼ Gamma( [2] [2] , 1/ [2] ) with [2] = exp( [2] [2] ),…”
Section: Data Description and Estimation Resultsmentioning
confidence: 99%
“…For the comparison of the quality of the various BMS systems, Oh et al [17] proposed the hypothetical mean square error (HMSE), a measure defined as the MSE between the aggregate severity and the BMS premium in the stationary state. For example, for the frequency-severity model in Section 2.2, we obtain HMSE( , −1/+ℎ) = E (E[ +1 | Λ [1] , Λ [2] , Θ [1] , Θ [2] ] − Λ [1] Λ [2] ( )) 1] )ℎ( [1] , [2] ) d [1] d [2] for a given relativity set = ( (0), .…”
Section: Comparison Of the Bmsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on real data emphasized in several cases the existence of a certain dependence that should be taken into account because it can affect important actuarial quantities like premiums and ruin probabilities. Therefore, alternative approaches incorporate dependence between the number of claims and their average severity, see, for example, Erhardt and Czado [1], Czado et al [2], Krämer et al [3], Lee and Shi [4], or Oh et al [5]. In this paper, we propose the bivariate Sarmanov distribution to analyze the joint behavior of the number of claims and of each one of the individual claim amounts, instead of their average; i.e., we consider heterogeneity between the claim amounts associated with each number of claims.…”
Section: Introductionmentioning
confidence: 99%
“…As a second application, a random effects model for correlated claim frequency and severity is worked out. While the existence of such a correlation and its economic significance is well documented in the literature (see e.g., Park, Kim, & Ahn, 2018), existing multivariate random effects based models capable of capturing dependence between claim frequency and severity typically suffer from computational intractability (see, e.g., Baumgartner, Gruber, & Czado, 2015; Czado & Gschlossl, 2007; Oh, Shi, & Ahn, 2020). Some recent papers try to evade this burden by letting the number of claims enter as a covariate in the severity model, without introducing random effect for the severity component (see, e.g., Garrido, Genest, & Schulz, 2016; Jeong, Valdez, Ahn, & Park, 2017; Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%